A 'light-up' intercalator displacement assay for detection of triplex DNA stabilizers. Issue 13 (21st January 2020) - del Mundo, Imee M. A.; Cho, Eun Jeong; Dalby, Kevin N.; Vasquez, Karen M.
Abstract : A 'light-up' intercalator displacement assay to detect binding of triplex ligands was developed and assessed for high-throughput screening applicability. Abstract : Here, we developed a coralyne-based, 'light-up' intercalator displacement assay to identify molecular stabilizers of triplex DNA using a sequence from a chromosomal breakpoint hotspot in the human c-MYC oncogene. Its potential to identify triplex DNA ligands was demonstrated using BePI and doxorubicin. Identification of triplex-interacting ligands may allow the regulation of genetic instability in human genomes.